Mechanics of post‐cam engagement during simulated dynamic activity. Issue 9 (19th April 2013) - Fitzpatrick, Clare K.; Clary, Chadd W.; Cyr, Adam J.; Maletsky, Lorin P.; Rullkoetter, Paul J.
Abstract Posterior‐stabilized (PS) total knee arthroplasty (TKA) components employ a tibial post and femoral cam mechanism to guide anteroposterior knee motion in lieu of the posterior cruciate ligament. Some PS TKA patients report a clicking sensation when the post and cam engage, while severe wear and fracture of the post; we hypothesize that these complications are associated with excessive impact velocity at engagement. We evaluated the effect of implant design on engagement dynamics of the post‐cam mechanism and resulting polyethylene stresses during dynamic activity. In vitro simulation of a knee bend activity was performed for four cadaveric specimens implanted with PS TKA components. Post‐cam engagement velocity and flexion angle at initial contact were determined. The experimental data were used to validate computational predictions of PS mechanics using the same loading conditions. A lower limb model was subsequently utilized to compare engagement mechanics of eight TKA designs, relating differences between implants to geometric design features. Flexion angle and post‐cam velocity at engagement demonstrated considerable ranges among designs (23°–89°, and 0.05–0.22 mm/°, respectively). Post‐cam velocity was correlated (r = 0.89) with tibiofemoral condylar design features. Condylar geometry, in addition to post‐cam geometry, played a significant role in minimizing engagement velocity and forces and stresses in the post. This analysis guides selection and design of PS implants that facilitate smooth post‐cam engagement and reduce edge loading of the post. © 2013 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 31:1438–1446, 2013